DAMPAK TENAGA KERJA ASING TERHADAP SOSIAL KEMASYARAKAT MASYARAKAT KOTA DUMAI - Fitratunnisa "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe about the the impact of foreign workers the social community in Dumai City. Labor in the city of Dumai come from various countries, and the majority come from the Chinese State. they come up with a good quality work. With the high mobility of labor between countries make Dumai City which became one of the cities in Indonesia are feeling the effects of the foreign workers.This study found that the presence of foreign workers in Dumai City provides a wide range of social impact in society, for the example can increase revenue (PAD), and improve the lives of people in Dumai. This of course has a positive impact on society and government of Dumai City.Keywords: Impact, Foreign Workers, Social Community, Institutionalization